2021
DOI: 10.3390/molecules26051496
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Charging Optimization of a Wavy-Shaped Nano-Enhanced Thermal Storage Unit

Abstract: A wavy shape was used to enhance the thermal heat transfer in a shell-tube latent heat thermal energy storage (LHTES) unit. The thermal storage unit was filled with CuO–coconut oil nano-enhanced phase change material (NePCM). The enthalpy-porosity approach was employed to model the phase change heat transfer in the presence of natural convection effects in the molten NePCM. The finite element method was applied to integrate the governing equations for fluid motion and phase change heat transfer. The impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…PCM has teeny temperature variation during the phase change process, low melting, and high latent heat. 47,48 Moraga et al 49 used four kinds of pure PCM to design a BTM to investigate the optimal number of layers and locations of PCMs. The study revealed that three layers of PCM is the optimal configuration where the PCMs with higher thermal conductivity should be placed closer to the battery while PCMs with lower thermal conductivity should be placed in the outer wall.…”
Section: Battery Thermal Management Systemsmentioning
confidence: 99%
“…PCM has teeny temperature variation during the phase change process, low melting, and high latent heat. 47,48 Moraga et al 49 used four kinds of pure PCM to design a BTM to investigate the optimal number of layers and locations of PCMs. The study revealed that three layers of PCM is the optimal configuration where the PCMs with higher thermal conductivity should be placed closer to the battery while PCMs with lower thermal conductivity should be placed in the outer wall.…”
Section: Battery Thermal Management Systemsmentioning
confidence: 99%